2021
DOI: 10.3389/fneur.2021.617526
|View full text |Cite
|
Sign up to set email alerts
|

Frequency and Predictors of Traumatic Encephalopathy Syndrome in a Prospective Cohort of Retired Professional Athletes

Abstract: Traumatic encephalopathy syndrome (TES) is proposed to represent the long-term impact of repetitive head-injury exposure and the clinical manifestation of chronic traumatic encephalopathy (CTE). This study aimed to evaluate the frequency of TES in a cohort of retired professional contact sport athletes, compare the frequency of TES to clinical consensus diagnoses, and identify predictors that increase the likelihood of TES diagnosis. Participants were 85 retired professional contact sport athletes from a prosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…After selection based on the pertinence and relevance to the topic of the review, 11,191 records were excluded, leaving 47 articles meeting the selection criteria. The full texts of the selected articles were assessed for inclusion, and 30 further articles were excluded as 3 were case reports [17,19,45], 1 review [46], 1 reported participation in sports as a leisure activity [47] 2 reported data only on an overall measure of physical activity [48,49] 2 included only athletes who had ≥ 1 head/brain injury [50,51] 8 did not report any measure of risk of NDs and/or NCDs [20,[52][53][54][55][56][57][58] and 13 were already included in the 2016 review [59][60][61][62][63][64][65][66][67][68][69][70][71].…”
Section: Resultsmentioning
confidence: 99%
“…After selection based on the pertinence and relevance to the topic of the review, 11,191 records were excluded, leaving 47 articles meeting the selection criteria. The full texts of the selected articles were assessed for inclusion, and 30 further articles were excluded as 3 were case reports [17,19,45], 1 review [46], 1 reported participation in sports as a leisure activity [47] 2 reported data only on an overall measure of physical activity [48,49] 2 included only athletes who had ≥ 1 head/brain injury [50,51] 8 did not report any measure of risk of NDs and/or NCDs [20,[52][53][54][55][56][57][58] and 13 were already included in the 2016 review [59][60][61][62][63][64][65][66][67][68][69][70][71].…”
Section: Resultsmentioning
confidence: 99%
“…The majority of research surrounding sleep and mental health in sport has previously focussed on competing athletes, with little focussed on retired athletes. Post-retirement research is saturated by an emphasis on comorbidities, such as concussion history and subsequent chronic traumatic encephalopathy ( Kerr et al, 2012 , 2014b ; Didehbani et al, 2013 ; Hart et al, 2013 ; Strain et al, 2013 ; Iverson, 2014 ; Hutchison et al, 2018 ; Hind et al, 2021 ; Schaffert et al, 2021 ), and obesity ( Hyman et al, 2012 ; Churchill et al, 2018 ). Further, this research is often limited to contact sport athletes, recruiting male dominated samples.…”
Section: Research Strategymentioning
confidence: 99%
“…While there has been a considerable amount of research separately examining sleep and mental health problems in current athletes ( Gulliver et al, 2014 ; Cheek et al, 2015 ; Kong and Harris, 2015 ; Rao and Hong, 2016 ; Swinbourne et al, 2016 ; Kilic et al, 2017 ; Malhotra, 2017 ; Thornton et al, 2017 ; Tuomilehto et al, 2017 ; Foskett and Longstaff, 2018 ; Castaldelli-Maia et al, 2019 ; Asplund and Chang, 2020 ; Caia et al, 2020 ; Timpka et al, 2021 ; Costa et al, 2022 ), almost none has examined the two areas together. Furthermore, although there is some research on mental health problems in retired athletes ( Kerr et al, 2014a ; Gouttebarge et al, 2016 ; Kilic et al, 2017 ; Fernandes et al, 2019 ; Mannes et al, 2019 ; Esopenko et al, 2020 ), little is known about mental health or sleep problems outside of comorbid conditions (i.e., concussion history, obesity) in ex-contact sport athletes ( Hyman et al, 2012 ; Kerr et al, 2012 , 2014b ; Didehbani et al, 2013 ; Hart et al, 2013 ; Strain et al, 2013 ; Iverson, 2014 ; Churchill et al, 2018 ; Hutchison et al, 2018 ; Hind et al, 2021 ; Schaffert et al, 2021 ). This is despite current and former athletes being susceptible to both sleep and mental health disorders ( Gouttebarge et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…In patients with dementia, TBI may influence cognitive and behavioral outcomes, 8 impacting quality of life and clinical diagnoses. 9 , 10 Perhaps due to underlying network dysfunction and/or the introduction of region‐specific vulnerabilities to neurodegeneration, growing evidence suggests that TBI affects phenotypes of neuropsychiatric symptoms (NPS) during progression to all‐cause dementia. 8 , 11 Importantly, NPS precede dementia diagnosis in many patients; 11 however, some research suggests that patients with TBI history (any severity) may have an earlier onset of anxiety symptoms and an elevated risk of apathy, motor disturbances, and disinhibition compared to those without.…”
Section: Introductionmentioning
confidence: 99%
“…6,7 In patients with dementia, TBI may influence cognitive and behavioral outcomes, 8 impacting quality of life and clinical diagnoses. 9,10 Perhaps due to underlying network dysfunction and/or the introduction of region-specific vulnerabilities to neurodegeneration, growing evidence suggests that TBI affects phenotypes of neuropsychiatric symptoms (NPS) during progression to all-cause dementia. 8,11 Importantly, NPS precede dementia diagnosis in many patients; 11 however, some research suggests that patients with TBI history (any severity)…”
Section: Introductionmentioning
confidence: 99%